Preliminary Screening of Selected Phytochemicals and Analysis of Essential Trace Elements in Boswellia serrata Roxb, Prosopis africana and Sclerocarya birrea: Plants with Therapeutic Potentials to Treat Hemorrhoids - ELISHA J. J, NUHU A. A, AGBAJI E. B, ABECHI S.E (Journal of Pure & Applied Sciences, 2019)
The use of herbal medicines is popular worldwide with about 80% of the world population relying on herbal medicines for their primary healthcare.  Plants are an important source of bioactive substances and many essential trace elements that play vital roles in general human well-being. Objective: The objective of this study is the preliminary screening of selected phytochemicals and analysis of essential trace elements in Boswellia serrata (Roxb), Prosopis africana (Guill & Perr) and Sclerocarya birrea (A.Rich) Hochst. The study also discuss the overall impact of Fe, Zn, Mn and Co and the selected phytochemicals on human health as the possible scientific basis for using the three popular medicinal plants in Zaria with therapeutic potentials to treat piles (Hemorrhoids). Methodology: The three most popular herbal medicines in Zaria obtained from stem barks of Boswellia serrata Roxb, Prosopis africana (Guill & Perr) and Sclerocarya birrea (A.Rich) Hochst were screened for alkaloids, saponins, terpenoids, phlobatannins, tannins, steroids and flavonoids using standard methods and iron, manganese, zinc and cobalt were analysed a long side reference standard material IAEA 1515 (apple leaves) using instrumental neutron activation analysis (INAA) technique. Results: Alkaloids, saponins, terpenoids, phlobatannins, tannins and steroids except flavonoids were detected in the three popular herbal medicines. The concentrations of Fe ranged between 87.90±11.7 and 652±21mg/kg, Mn, 15.7±0.7 and 49.70±1.40 mg/kg; Zn, 2.90±10 and 8.08±1.21 mg/kg and Co, 0.045±0.05 and 0.16±0.01 mg/kg. The concentrations of essential trace elements in the herbal medicines were in the increasing order of Prosopis africana > Boswellia serrata > Sclerocarya birrea and the magnitude of essential trace elements was Fe > Mn > Zn > Co. Conclusion: These results suggest potential efficacy of the three popular herbal medicines to be used in treating human ailments.